DEFENDERS OF DIGNITY: THE ROLE OF NGOs IN SUPPORTING DISABLED CHILDREN IN INDIA - Thomas, Subin; Thankalayam, Sheen; Kamath, Parashurama; Ninan, Neenu Anna (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Children are considered precious gifts and hold the key to the future of any nation. They represent hope, potential and the promise of a better tomorrow. Access to education, healthcare, nutrition and opportunities for social and emotional progress are essential for the holistic development of children. However, children with disabilities struggle to access these rights and explore their inner potential. Using the term ‘differently abled children’ instead of ‘disabled children’ is a more inclusive and respectful way to refer to children with disabilities or special needs. Despite their challenges, these children have unique abilities and strengths and focus on their capabilities rather than their limitations. Governments and NGOs are continually working to address the challenges encountered by differently abled children in India and to create a more inclusive and supportive environment for their development and growth. In India, NGOs are crucial in assisting the government and other institutions in their efforts to protect and support children with disabilities. Their effort and dedication considerably improve the lives of differently abled children and advance an inclusive and equitable society. The research paper provides an overview of the current issues confronting disabled children in India, such as societal stigma, limited access to resources and other barriers. It emphasizes the crucial role of NGOs as ‘defenders of dignity’ in addressing the challenges faced by disabled children in India.